1992
DOI: 10.1002/1098-108x(199207)12:1<47::aid-eat2260120107>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Risk of infection and immune function in anorexia nervosa

Abstract: The eating disorder, anorexia nervosa, like other forms of starvation, has been associated with an increased risk and severity of infectious diseases. However, there is conflicting evidence about the true risk of infection in anorectic patients. Indeed, some anorectics appear to be less susceptible to minor viral illnesses, possibly analagous to the attenuation of viral infections observed in protein‐starved mice. Leukopenia and neutrophil dysfunction, including abnormal chemotaxis and depressed microbicidal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…Our findings are consistent with previous studies of anorectics which reported that many aspects of immunity are well preserved and may even be enhanced in anorexia nervosa patients (Bentdal et al, 1991;Brambilla et al, 1993;Golla et al, 1981;Pertschuk, Crosby, Barot, & Mullen, 1982). However, some laboratory parameters of cellmediated immunity, especially anergy to delayed-type hypersensitivity skin testing, have also been reported (Pomeroy, Mitchell, & Eckert, 1992). Enhancement of cell-mediated immunity has also been reported in obese patients on a VLCD (McMurray et al, 1990).…”
Section: I Sc U Ssl Onsupporting
confidence: 92%
“…Our findings are consistent with previous studies of anorectics which reported that many aspects of immunity are well preserved and may even be enhanced in anorexia nervosa patients (Bentdal et al, 1991;Brambilla et al, 1993;Golla et al, 1981;Pertschuk, Crosby, Barot, & Mullen, 1982). However, some laboratory parameters of cellmediated immunity, especially anergy to delayed-type hypersensitivity skin testing, have also been reported (Pomeroy, Mitchell, & Eckert, 1992). Enhancement of cell-mediated immunity has also been reported in obese patients on a VLCD (McMurray et al, 1990).…”
Section: I Sc U Ssl Onsupporting
confidence: 92%
“…These findings would suggest that body weight itself plays a role in determining levels of alternative pathway complement components. Interestingly, the low complement values observed in starving anorectics did not predispose these extremely low-weight patients to infection [25]. Although complement levels of anorectics were significantly decreased, the levels were apparently not low enough to increase infection risk, i.e.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, patients with AN have been observed to be relatively protected from infection (Pomeroy, Mitchell, & Eckert, 1992;Bowers & Eckert, 1978). This is the case even though many abnormalities in the function of the immune system have been found in AN subjects including leukopenia (Kay & Stricker, 1983), low CD4+ counts (Pirke, Nerl, & Fichter, 1992), low CD8+ counts (Fink, Eckert, Mitchell, Crosby, & Pomeroy, 1996), and abnormal levels of many of the cytokines (Pomeroy et al, 1994;Polack et al, 1993;Schattner, Tepper, Steinbock, Hahn, & Schoenfeld, 1990;Bessler et al, 1993;Vaisman & Hahn, 1991).…”
Section: Introductionmentioning
confidence: 99%